Identification of early cardiac dysfunction and heterogeneity after pressure and volume overload in mice by high-frequency echocardiographic strain imaging - Xu, Ran; Ding, Zhiwen; Li, Hao; Shi, Jing; Cheng, Leilei; Xu, Huixiong; Wu, Jian; Zou, Yunzeng (Frontiers in Cardiovascular Medicine, 2023)
Object: Aortic stenosis and regurgitation are clinically important conditions characterized with different hypertrophic types induced by pressure or volume overload, respectively, but with comparable cardiac function in compensated stage. Speckle-tracking based strain imaging has been applied to assess subtle alterations in cardiac abnormality, but its application in differentiating these two types of ventricular hypertrophy is still sparse. Here, we performed strain imaging analysis of cardiac remodeling in these two loading conditions. Methods: C57BL/6J mice were subjected to transverse aortic constriction (TAC)-induced pressure overload or aortic regurgitation (AR)-induced volume overload. Conventional echocardiography and strain imaging were comprehensively assessed to detect stimulus-specific alterations in TAC and AR hearts. Results: Conventional echocardiography did not detect significant changes in left ventricular systolic (ejection fraction and fractional shortening) and diastolic (E/E’) function in either TAC or AR mice. On the contrary, global strain analysis revealed global longitudinal strain and strain rate were remarkably impaired in TAC while preserved in AR mice, although global radial, and circumferential strain and strain rate were significantly reduced in both models. Regional strain analysis in the long axis demonstrated that longitudinal strain and strain rate in all or most segments were decreased in TAC but maintained or slightly dented in AR mice, while radial strain and strain rate indicated overt decline in both models. Moreover, decreased radial and circumferential strain and strain rate were observed in most segments of TAC and AR mice in the short axis. Conclusion: Strain imaging is superior to conventional echocardiography to detect subtle changes in myocardial deformation, with longitudinal strain and strain rate indicating distinct functional changes in pressure versus volume overload myocardial hypertrophy, making it potentially an advanced approach for early detection and differential diagnosis of cardiac dysfunction.